An integrated and secured medical data framework for effective tele health applications. (16th December 2020) - Vallathan, G.; Jayanthi, K.
The rapid progression of healthcare technologies and transmission strategies makes the system reliable to gain, dispense and manage data over medical devices and as well improves conventional hospital information systems (HIS) to deliver effective healthcare services. When the patient medical information is communicated through wireless network, there exists a high chance of modifying the information. Therefore, a futuristic tele healthcare framework has been proposed to ensure the security, data integrity, quality and minimisation of bandwidth requirements for offering complete healthcare services at reduced cost. The proposed framework encompasses the integration of three modules viz. steganography, compression and encryption. This framework also validates the integrity of ROI, furthermore it ensures better compression ratio. Finally, the whole image is encrypted with modified chaotic map encryption in order to afford complete medical data security. Experimental outcomes demonstrate that the proposed framework offers robustness in terms of security, quality and reliability which alleviate misdiagnosis at the physician end in telemedicine applications.